Nylon super-bright bark wrinkled fabric and manufacturing process thereof

By adopting a composite layer structure in nylon fabric, including nylon 20D embryo cloth, sterilization and anti-static layer, warmth layer and anti-fouling waterproof layer, the shortcomings of existing nylon fabrics in bark wrinkle effect and performance are solved, and high Performance nylon super bright bark wrinkle fabric.

CN119427851AActive Publication Date: 2025-02-14JINJIANG LONGXINGLONG DYEING & WEAVING INDALCO

Patent Information

Application Number
CN202411489052.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-14
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

When preparing bark wrinkles, existing nylon fabrics have problems such as uneven wrinkles, insufficient gloss, and hard feel. Moreover, the nylon material has high hygroscopicity, poor dimensional stability, no antibacterial function, and poor antifouling performance. It is prone to static electricity.

Method used

The structure of germ cloth layer, sterilization and anti-static layer, warm layer, and anti-fouling and waterproof layer is adopted. The germ cloth layer uses nylon 20D embryo cloth, and the sterilization and anti-static layer is 50% anti-static fiber and 50% sterilization fiber. The blended fabric has a thermal insulation layer with spray-coated aerogel, and the anti-fouling waterproof layer is treated with fluoride-free waterproofing agent Rudolph ECO.

Benefits of technology

It realizes the excellent waterproof and stain-proof, sterilization and anti-static properties of the fabric, preventing fluff from falling off and anti-pilling, and has durable gloss, wrinkle style and excellent warmth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119427851A_ABST
    Figure CN119427851A_ABST
Patent Text Reader

Abstract

The invention relates to a nylon super-bright bark wrinkle fabric and a manufacturing process thereof, and belongs to the technical field of nylon fabrics, the nylon super-bright bark wrinkle fabric comprises a gray cloth layer, a degerming anti-static layer, a warm-keeping layer and an antifouling waterproof layer which are compounded in sequence, the gray cloth layer and the degerming anti-static layer are compounded and connected through a bonding layer, the gray cloth layer adopts nylon 20D gray cloth and the degerming anti-static layer, and the degerming anti-static layer adopts nylon 20D gray cloth. The fabric is a blended fabric formed by blending 50% of anti-static fibers and 50% of degerming fibers, the bonding layer is composed of a plurality of parallel hot melt adhesive films, the warm-keeping layer is formed by spraying a layer of aerogel on the outer portion of the degerming anti-static layer, and the antifouling and waterproof layer is formed by baking the whole fabric after the whole fabric is soaked with a fluoride-free waterproof agent rudoff ECO. The fabric cover has excellent waterproof, antifouling, antibacterial, antistatic, fluff-shedding-resistant and anti-pilling characteristics, has durable gloss, wrinkling style and thermal insulation performance, is very suitable for being used as fabrics of fashionable down jackets, wind coats and jackets, and meets the pursuit of consumers for fashion and quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nylon fabrics, in particular to a nylon super-bright bark wrinkle fabric and a manufacturing process thereof. Background Art

[0002] With the development of economy and the continuous improvement of people's living standards, the textile fabric industry is facing unprecedented challenges and opportunities. Consumers' demand for textile fabrics is no longer limited to basic wearing functions, but pays more attention to the visual beauty, physical comfort and versatility of fabrics. Especially in the fields of outdoor sports, fashion apparel and high-end home decoration, higher requirements are put forward for the waterproof, down-proof, warm and durable properties of textile fabrics. In recent years, a kind of fabric imitating bark texture has appeared on the market, namely bark wrinkle fabric, which is deeply loved by consumers for its unique texture and three-dimensional sense. However, most of the bark wrinkle fabrics on the market are made of cotton, polyester and other materials, which are difficult to compare with nylon in glossiness and wear resistance. Traditional Although nylon fabrics have excellent wear resistance, chemical resistance and self-lubrication, they are limited in glossiness and texture diversity, and are difficult to meet the market's pursuit of high-end, personalized fabrics. In the prior art, the processing of nylon fabrics usually includes desizing, dyeing, drying and other steps. However, when preparing fabrics with bark wrinkle effects, there are often problems such as uneven bark wrinkles, insufficient glossiness, and hard hand feel. These problems not only affect the appearance of the fabric, but also reduce its wearing comfort. In addition, due to the special properties of nylon materials, such as high hygroscopicity, poor dimensional stability, no antibacterial function, poor antifouling performance, etc., nylon materials are prone to generate static electricity during use, which affects wearing comfort and easily causes suede to catch fire. Summary of the invention

[0003] In order to overcome the technical defects of the prior art, the present invention provides a nylon super-bright bark wrinkle fabric and a production process thereof. During the preparation, the fault tolerance rate is high, and after the preparation is completed, the fabric surface has excellent waterproof and anti-fouling, sterilization and anti-static, and anti-fluff and anti-pilling properties, and also has the advantages of durable gloss and wrinkle style and excellent warmth retention performance.

[0004] The technical solution adopted by the present invention is: a nylon super bright bark wrinkle fabric, including a grey cloth layer, a sterilization and antistatic layer, a thermal insulation layer, and an antifouling and waterproof layer which are compounded in sequence. The grey cloth layer and the sterilization and antistatic layer are compounded and connected by an adhesive layer. The grey cloth layer is made of nylon 20D grey cloth. The sterilization and antistatic layer is a blended fabric made by blending 50% antistatic fiber and 50% sterilization fiber. Air holes are left in the middle during blending. The blending of the antistatic fiber and the sterilization fiber can ensure that the fabric has antistatic and sterilization properties while being light and thin. The adhesive layer is composed of multiple parallel hot melt adhesive films. The thermal insulation layer is a layer of aerogel sprayed on the outside of the sterilization and antistatic layer. The antifouling and waterproof layer is formed by baking the entire fabric after the fluorine-free waterproofing agent Rudolf ECO is impregnated.

[0005] Preferably, in order to ensure that a grey cloth with a certain thickness, softness and air permeability is obtained, the nylon 20D grey cloth is woven from nylon filament blanks with a warp density of 225 and a weft density of 180, and the nylon filaments are prepared by a melt spinning method of a polyamide resin. During the spinning process, the polyamide resin is heated to a molten state and then extruded through the spinneret holes of a spinning machine to form continuous filaments. The spinning speed adopts high-speed spinning of more than 3000 m / min. The nylon material has good wear resistance, and the nylon material also has good resistance to mold. The nylon filament grey cloth is easy to carry out subsequent dyeing, printing and other treatments, and the grey cloth has good physical properties such as tensile strength, elongation at break and elastic recovery rate.

[0006] Preferably, in order to add an anti-static function to the fabric, the anti-static fiber is a stainless steel metal conductive fiber, which is made of high-purity, highly corrosion-resistant stainless steel through multiple steps such as smelting and casting, rolling and drawing, heat treatment, surface treatment and coating. The stainless steel metal conductive fiber has good electrical conductivity and can quickly conduct static charge into the ground, thereby effectively preventing static electricity accumulation.

[0007] Preferably, in order to blend the sterilization material with the antistatic fiber to make a sterilization antistatic fabric, this method can ensure that the sterilization material is evenly distributed in the fiber, thereby giving the fabric a long-lasting sterilization property. The sterilization fiber is one or more of nano silver ion fiber, bamboo charcoal fiber, and chitin fiber.

[0008] A process for producing super bright nylon bark wrinkle fabric comprises the following steps: Step 1: Fabric distribution: The grey cloth layer and the antibacterial and antistatic layer are woven separately, and then bonded by the hot melt adhesive film of the bonding layer.

[0009] Step 2, desizing: Desizing the prepared fabric at a temperature of 90-95℃ and a speed of 50-60m / min, and add the following additives in order according to the amount of water, that is, add per liter of water: add chelating agent 1-4g / l at a uniform speed within 5-10 minutes; add liquid alkali 15-20g / l at a uniform speed within 5-10 minutes; add sodium dodecyl sulfonate 3-6g / l as a refining agent at a uniform speed within 5-10 minutes; Step 3: Shape: bake the desized fabric at 170℃ at a speed of 40-50 yards / minute; Step 4: Calendering: Calender the shaped fabric for 5 times at a temperature of 170 degrees and a speed of 20m / min. The purpose is to make the fabric have excellent anti-velvet effect and super gloss after multiple high-temperature calendering treatments, and prevent extinction in the subsequent dyeing process; Step 5: Dyeing: Add auxiliaries and acid dyes to the calendered fabric in accordance with the amount of water per liter; dyeing temperature is 100 degrees; keep the temperature for 30-45 minutes; Step 6: Fixing: Add additives to the dyed fabrics according to the amount of water per liter during the fixing process, the temperature is 80 degrees; keep warm for 30 minutes; Step 7: Drying: Dry the fixed fabric for subsequent processing at a temperature of 120-130°C and a drying speed of 50-70 yards per minute. Step 8: Apply the thermal insulation layer: Apply the mixed aerogel coating evenly onto the surface of the dried fabric; Step 9: Shaping: Add 4-6% of the total liquid volume of waterproofing agent (Rudolf ECO) to a certain amount of water, and bake at 170℃ at a speed of 40-50 yards per minute.

[0010] Preferably, in step one, in order to ensure that the stainless steel metal conductive fiber has good conductivity and antistatic effect, and to ensure its compatibility with the antistatic fiber, for the weaving of the sterilization antistatic layer, the antistatic fiber and the sterilization fiber must first be pretreated, such as washing, drying, etc., to remove surface impurities and moisture. Secondly, special attention should be paid not to damage the conductivity and bactericidal properties of the fiber. During blending, special blending equipment is used to mix the antistatic fiber and the sterilization fiber at 50% each. During the blending process, the uniform distribution of the fibers must be ensured to avoid the occurrence of fiber clumps or uneven distribution. Finally, the blended fibers are spun to make yarn. During the spinning process, an appropriate amount of wool oil or other additives can be added as needed to reduce the generation of static electricity and improve the quality of the yarn.

[0011] Preferably, in step eight, in order to ensure that the coating has a smooth appearance without bulging, cracks, delamination, etc., the surface of the fabric base layer should be thoroughly cleaned before applying the aerogel coating to remove impurities such as oil stains and floating dust, and the fabric base layer should be polished to ensure that the surface is flat, without bumps or bulges, and the surface of the fabric base layer should be completely dry without any moisture residue.

[0012] Preferably, in step eight, in order to strictly control the coating mixing ratio and coating thickness, when applying the aerogel coating, it should be noted that the coating should be applied from top to bottom, first on the details and then on the large surface, to ensure that the coating is uniform and without any omissions. The thickness of the first coat is controlled between 0.5-1 mm, and the second coat is applied after it is completely dry. The second coat thickness is less than 1 mm, ensuring that the total thickness meets the design requirements (generally less than 2 mm).

[0013] The beneficial effects of the present invention are as follows: the present invention selects environmentally friendly nylon materials to reduce environmental pollution in the production process, which meets the needs of modern people for green consumption; the nylon 20D grey cloth can ensure good wear resistance while having good softness and air permeability, is not easy to mold, and is easy to be subsequently treated by dyeing, printing, etc.; moreover, the sterilization and antistatic layer, the thermal insulation layer, and the antifouling and waterproof layer added to the grey cloth can make the fabric have excellent waterproof and antifouling, sterilization and antistatic, and anti-fluff and anti-pilling properties; in the fabric manufacturing process of the present invention, the grey cloth is calendered multiple times, which can make the fabric have a durable gloss and a wrinkled style, and is very suitable for fabrics of fashionable down coats, windbreakers, and jackets, satisfying consumers' pursuit of fashion and quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a schematic diagram of the layered structure of the present invention.

[0015] Figure 2 This is a schematic diagram of the structure of the sterilization and antistatic layer of the present invention.

[0016] Figure 3 It is a schematic diagram of the weft-direction cross-sectional structure of the grey cloth layer of the present invention.

[0017] Figure 4 The figure is a schematic diagram of the process flow of the present invention.

[0018] Figure 5 This is a performance test diagram of the present invention.

[0019] Explanation of the accompanying drawings: In the figure: 1, grey cloth layer; 2, adhesive layer; 3, antibacterial and antistatic layer; 4, thermal insulation layer; 5, antifouling and waterproof layer; 6, warp; 7, weft; 8, air vents. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with the accompanying drawings: Example 1

[0021] like Figure 1-3 As shown, this embodiment provides a nylon super bright bark wrinkle fabric, including a composite cloth layer 1, a sterilization and antistatic layer 3, a thermal insulation layer 4, and an antifouling and waterproof layer 5, the cloth layer 1 and the sterilization and antistatic layer 3 are compositely connected by an adhesive layer 2, the cloth layer 1 is made of nylon 20D cloth, which can ensure softness and breathability while making the cloth have the characteristics of wear resistance and easy coloring, the sterilization and antistatic layer 3 is a blended fabric made of 50% antistatic fiber and 50% sterilization fiber, and a gap is left in the middle during blending. The air holes 8 are made of a blend of antistatic fiber and antibacterial fiber to ensure that the fabric has antistatic and antibacterial properties while being light and thin. The adhesive layer 2 is composed of multiple parallel hot-melt adhesive films, which can bond multiple layers of fabrics. The thermal insulation layer 4 is a layer of aerogel sprayed on the outside of the antibacterial and antistatic layer 3, which can make the grey cloth have better thermal insulation functions. The anti-fouling and waterproof layer 5 is formed by baking the entire fabric after impregnating it with the fluorine-free waterproof agent Rudolf ECO, so that the fabric as a whole has waterproof and anti-fouling properties.

[0022] Nylon 20D grey cloth is woven with nylon filament blanks with a warp density of 225 and a weft density of 180. During the weaving process, the density of warp 6 and weft 7 can be adjusted as needed to obtain grey cloths with different thickness, softness and breathability. Nylon filaments are prepared by melt spinning of polyamide resin. During the spinning process, the polyamide resin is heated to a molten state and then extruded through the spinneret holes of the spinning machine to form continuous filaments. The spinning speed adopts high-speed spinning of more than 3000m / min. Nylon material has good wear resistance, which makes the nylon filament grey cloth not easy to wear in long-term use. Nylon material also has good resistance to mold, which makes the grey cloth not easy to mold. Nylon filament grey cloth is easy to carry out subsequent dyeing, printing and other treatments to meet different market needs. The grey cloth has good physical properties such as tensile strength, elongation at break and elastic recovery rate.

[0023] Anti-static fiber is stainless steel metal conductive fiber. Stainless steel metal conductive fiber is made of high-purity, high-corrosion-resistant stainless steel through multiple steps such as smelting and casting, rolling and drawing, heat treatment, surface treatment and coating. This ensures that anti-static function is added to the fabric. Stainless steel metal conductive fiber has good conductive properties and can quickly conduct static charge into the ground, thereby effectively preventing static electricity accumulation.

[0024] The antibacterial fiber uses nano-silver ion fiber, so that the antibacterial material can be blended with the antistatic fiber to make antibacterial and antistatic fabrics. This method can ensure that the antibacterial material is evenly distributed in the fiber, thereby giving the fabric lasting antibacterial properties. The antibacterial effect of nano-silver ion fiber is very significant. Nano-silver ions can destroy the cell structure of bacteria and combine with sulfur atoms in bacterial proteins to inactivate bacteria, thereby achieving the purpose of sterilization. Studies have shown that nano-silver ions can kill hundreds of pathogenic microorganisms, including antibiotic-resistant bacteria. In the field of medical and health care, nano-silver ions are widely used in various antibacterial products, such as medical dressings, disinfectants, etc.

[0025] A process for producing super bright nylon bark wrinkle fabric comprises the following steps: Step 1: Distribution: The grey cloth layer 1 and the antibacterial and antistatic layer 3 are woven separately, and then bonded by the hot melt adhesive film of the bonding layer 2.

[0026] Step 2, desizing: Desizing the prepared fabric at a temperature of 90-95℃ and a speed of 50-60m / min, and add the following additives in order according to the amount of water, that is, add per liter of water: add chelating agent 1-4g / l at a uniform speed within 5-10 minutes; add liquid alkali 15-20g / l at a uniform speed within 5-10 minutes; add sodium dodecyl sulfonate 3-6g / l as a refining agent at a uniform speed within 5-10 minutes; Step 3: Shape: bake the desized fabric at 170℃ at a speed of 40-50 yards / minute; Step 4: Calendering: Calender the shaped fabric for 5 times at a temperature of 170 degrees and a speed of 20m / min. The purpose is to make the fabric have excellent anti-velvet effect and super gloss after multiple high-temperature calendering treatments, and prevent extinction in the subsequent dyeing process; Step 5: Dyeing: Add auxiliaries and acid dyes to the calendered fabric in accordance with the amount of water per liter; dyeing temperature is 100 degrees; keep the temperature for 30-45 minutes; Step 6: Fixing: Add additives to the dyed fabrics according to the amount of water per liter during the fixing process, the temperature is 80 degrees; keep warm for 30 minutes; Step 7: Drying: Dry the fixed fabric for subsequent processing at a temperature of 120-130°C and a drying speed of 50-70 yards per minute. Step 8: Apply the thermal insulation layer 4: Apply the mixed aerogel coating evenly onto the surface of the dried fabric; Step 9: Shaping: Add 4-6% of the total liquid volume of waterproofing agent (Rudolf ECO) to a certain amount of water, and bake at 170℃ at a speed of 40-50 yards per minute.

[0027] In step one, for the weaving of the anti-static layer 3, the anti-static fiber and the anti-bacterial fiber must first be pretreated, such as washing and drying, to remove surface impurities and moisture. The specifications and performance of the stainless steel metal conductive fiber can be determined to ensure that it has good conductivity and anti-static effect. It is also necessary to check the various quality indicators of the anti-bacterial fiber to ensure its compatibility with the anti-static fiber. Secondly, special attention should be paid to not damage the conductivity and bactericidal properties of the fiber. Special blending equipment is used for blending, and the anti-static fiber and the anti-bacterial fiber are mixed at 50% each. During the blending process, the uniform distribution of the fibers must be ensured to avoid the occurrence of fiber clumps or uneven distribution. Finally, the blended fibers are spun to make yarn. During the spinning process, an appropriate amount of wool oil or other additives can be added as needed to reduce the generation of static electricity and improve the quality of the yarn.

[0028] In step eight, before applying the aerogel coating, the surface of the fabric base layer should be thoroughly cleaned to remove impurities such as oil, dust, etc., and the fabric base layer should be polished to ensure that the surface is flat, without bumps or bulges. It is also necessary to ensure that the surface of the fabric base layer is completely dry and free of moisture residue, so as to ensure that the coating has a flat and smooth appearance without bulging, cracks, delamination, etc.

[0029] In step eight, when applying aerogel coating, it should be noted that the coating should be applied from top to bottom, from details to large surfaces, to ensure that the coating is even and without omissions. The thickness of the first coat should be controlled between 0.5-1mm. After it is completely dry, apply the second coat. The thickness of the second coat should be less than 1mm to ensure that the total thickness meets the design requirements (generally less than 2mm). In this way, the coating mixing ratio and coating thickness can be strictly controlled to ensure that the fabric has a certain performance insulation effect.

[0030] After the preparation is completed, the performance test is carried out, and the results are as follows Figure 3 shown. Example 2

[0031] like Figure 1-3 As shown, this embodiment provides a high-light-transmittance ceramic and a preparation process thereof. Compared with Example 1, the difference from Example 1 is that the antibacterial fiber in the antibacterial and antistatic layer 3 is made of bamboo charcoal fiber. The bamboo charcoal fiber has a certain antibacterial effect, but its specific antibacterial rate may vary due to different products and production processes. According to the test of SGS, an authoritative Chinese organization, the bacteria reduction rate of bamboo charcoal fiber under specific conditions (such as after 24 hours) can reach 95%, which shows that it has good antibacterial properties. The antibacterial effect of bamboo charcoal fiber is mainly due to its adsorption capacity and the release of far-infrared negative ions. These characteristics help to create an environment that is not conducive to bacterial growth.

[0032] The preparation steps are the same as those in Example 1.

[0033] After the preparation is completed, the performance test is carried out, and the results are as follows Figure 3 shown. Example 3

[0034] like Figure 1-3 As shown, this embodiment provides high-transmittance ceramics and a preparation process thereof. Compared with Example 1, the difference from Example 1 is that the antibacterial fiber in the antibacterial and antistatic layer 3 is chitin fiber. Chitin fiber has a strong inhibitory effect on bacteria, with an inhibition rate of more than 90%. The antibacterial mechanism of chitin fiber is mainly to adsorb bacteria through the positively charged amino groups in its molecules, and combine with the anionic components of its cell wall membrane protein to hinder bacterial growth and synthesis, leading to bacterial death. Chitin fiber is widely used in medical textiles, infant clothing and other fields due to its excellent antibacterial properties and biocompatibility.

[0035] The preparation steps are the same as those in Example 1.

[0036] After the preparation is completed, the performance test is carried out, and the results are as follows Figure 3 shown.

[0037] Comparative Example 1 like Figure 1-3 As shown, this embodiment provides high-transmittance ceramics and their preparation process. Compared with Example 1, the difference from Example 1 is that no sterilizing fiber is used in the sterilizing and antistatic layer 3, and all of them are woven from stainless steel metal conductive fibers, and the weaving process and specifications remain unchanged.

[0038] The preparation steps are the same as those in Example 1.

[0039] After the preparation is completed, the performance test is carried out, and the results are as follows Figure 3 shown.

[0040] Combining the test data of Examples 1 to 3 and comparing them with Comparative Example 1, the antibacterial effects of Examples 1 to 3 are far better than those of Comparative Example 1. For the antibacterial rate test after the fabric is washed for 24 hours, the antibacterial effect of Example 1 is the best, the antibacterial effect of Example 3 is second, and the antibacterial effect of Example 2 is average. Therefore, the fabric with the antibacterial and antistatic layer 3 added has an obvious antibacterial effect in actual use, and the fabric made of nano silver ion fiber has the best antibacterial effect.

[0041] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which shall fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A nylon super bright bark wrinkle fabric, characterized by: The invention comprises a grey cloth layer (1), a sterilizing and antistatic layer (3), a thermal insulation layer (4), and an antifouling and waterproof layer (5) which are compounded in sequence. The grey cloth layer (1) and the sterilizing and antistatic layer (3) are compounded and connected via an adhesive layer (2). The grey cloth layer (1) is made of nylon 20D grey cloth. The sterilizing and antistatic layer (3) is a blended fabric made by blending 50% of antistatic fiber and 50% of sterilizing fiber. The adhesive layer (2) is composed of a plurality of parallel hot melt adhesive films. The thermal insulation layer (4) is a layer of aerogel sprayed on the outside of the sterilizing and antistatic layer (3). The antifouling and waterproof layer (5) is formed by baking the entire fabric after impregnating it with a fluorine-free waterproof agent Rudolf ECO.

2. The nylon super bright bark wrinkle fabric according to claim 1, characterized in that: The nylon 20D grey cloth is woven from nylon filament blanks with a warp density of 225 and a weft density of 180. The nylon filaments are prepared by a melt spinning method of a polyamide resin. During the spinning process, the polyamide resin is heated to a molten state and then extruded through a spinneret of a spinning machine to form continuous filaments. The spinning speed is high-speed spinning of more than 3000 m / min.

3. The nylon super bright bark wrinkle fabric according to claim 1, characterized in that: The antistatic fiber is a stainless steel metal conductive fiber, which is made of high-purity, high-corrosion-resistant stainless steel through multiple steps such as smelting and casting, rolling and drawing, heat treatment, surface treatment and coating.

4. The nylon super bright bark wrinkle fabric according to claim 1, characterized in that: The sterilization fiber is one or more of nano silver ion fiber, bamboo charcoal fiber and chitin fiber.

5. A process for producing super bright nylon bark wrinkle fabric, characterized in that: The following steps are involved: Step 1: Fabrication: The embryonic fabric layer (1) and the antibacterial and antistatic layer (3) are woven separately, and then bonded together using the hot melt adhesive film of the bonding layer (2); Step 2, desizing: Desizing the prepared fabric at a temperature of 90-95℃ and a speed of 50-60m / min, and add the following additives in order according to the amount of water, that is, add per liter of water: add chelating agent 1-4g / l at a uniform speed within 5-10 minutes; add liquid alkali 15-20g / l at a uniform speed within 5-10 minutes; add sodium dodecyl sulfonate 3-6g / l as a refining agent at a uniform speed within 5-10 minutes; Step 3: Shape: bake the desized fabric at 170℃ at a speed of 40-50 yards / minute; Step 4: Calendering: Calender the shaped fabric for 5 times at a temperature of 170 degrees and a speed of 20m / min. The purpose is to make the fabric have excellent anti-velvet effect and super gloss after multiple high-temperature calendering treatments, and prevent extinction in the subsequent dyeing process; Step 5: Dyeing: Add auxiliaries and acid dyes to the calendered fabric in accordance with the amount of water per liter; dyeing temperature is 100 degrees; keep the temperature for 30-45 minutes; Step 6: Fixing: Add additives to the dyed fabrics according to the amount of water per liter during the fixing process, and the temperature is 80 degrees; Keep warm for 30 minutes; Step 7: Drying: Dry the fixed fabric for subsequent processing at a temperature of 120-130°C and a drying speed of 50-70 yards per minute. Step 8: Applying a thermal insulation layer (4): Apply the mixed aerogel coating evenly onto the surface of the dried fabric; Step 9: Shaping: Add 4-6% of the total liquid volume of waterproofing agent (Rudolf ECO) to a certain amount of water, and bake at 170℃ at a speed of 40-50 yards per minute.

6. The process for producing super bright nylon bark wrinkle fabric according to claim 5, characterized in that: In step one, for the weaving of the antibacterial antistatic layer (3), the antistatic fiber and the antibacterial fiber are firstly pretreated, such as washing and drying, to remove surface impurities and moisture. Secondly, special attention should be paid to not damaging the conductivity and bactericidal properties of the fibers. During blending, a dedicated blending device is used to mix the antistatic fiber and the antibacterial fiber at 50% each. During the blending process, the uniform distribution of the fibers is ensured to avoid the formation of fiber clumps or uneven distribution. Finally, the blended fibers are spun to make yarn. During the spinning process, an appropriate amount of wool oil or other additives can be added as needed to reduce the generation of static electricity and improve the quality of the yarn.

7. The process for producing super bright nylon bark wrinkle fabric according to claim 5, characterized in that: In step eight, before applying the aerogel coating, the surface of the fabric base layer should be thoroughly cleaned to remove impurities such as oil, dust, etc., and the fabric base layer should be polished to ensure that the surface is flat, without bumps or bulges, and that the surface of the fabric base layer is completely dry without any moisture residue.

8. The process for producing super bright nylon bark wrinkle fabric according to claim 5, characterized in that: In step eight, when applying the aerogel coating, it should be noted that the coating should be applied from top to bottom, first the details and then the large surface, to ensure that the coating is even and without any omissions. The thickness of the first coat is controlled between 0.5-1mm. After it is completely dry, apply the second coat. The thickness of the second coat is less than 1mm to ensure that the total thickness meets the design requirements.

Citation Information

Patent Citations

  • Process for manufacturing high-water-pressure-resistance and high-tearing PU (polyurethane) coated fabrics

    CN109137550A

  • Polyester-cotton interwoven one-way moisture-wicking yarn-dyed fabric and dyeing and finishing processing method thereof

    CN110747566A

  • Fluorine-free three-proofing fabric as well as preparation method and application thereof

    CN117344539A

  • Bacteriostatic anti-static messy hemp fabric

    CN215662172U

  • Anti-wrinkle aerogel down-filled fabric with high heat retention property

    CN216885549U

Cited By

  • Skin-tendering nylon warp elastic taslon fabric and manufacturing process thereof

    CN119974694A